2023
DOI: 10.1007/s00401-023-02552-6
|View full text |Cite
|
Sign up to set email alerts
|

IL-10-providing B cells govern pro-inflammatory activity of macrophages and microglia in CNS autoimmunity

Abstract: B cells contribute to chronic inflammatory conditions as source of antibody-secreting plasma cells and as antigen-presenting cells activating T cells, making anti-CD20-mediated B cell depletion a widely used therapeutic option. B cells or B cell subsets may, however, exert regulatory effects, while to date, the immunological and/or clinical impact of these observations remained unclear. We found that in multiple sclerosis (MS) patients, B cells contain regulatory features and that their removal enhanced activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…To confirm changes in TNFα expression at the protein level, we enriched CD14 + or CD16 + monocytes from cryopreserved PBMCs and showed that LPS-stimulated monocytes from MS patients expressed more TNFα post B cell depletion (Fig 5d). Increases of TNFα production by LPS-stimulated CD14 + cells was similarly observed in MS patients treated with ocrelizumab by another group 30 . However, there was no significant difference in TNFα ELISA using culture supernatant (data not shown).…”
Section: Resultsmentioning
confidence: 58%
“…To confirm changes in TNFα expression at the protein level, we enriched CD14 + or CD16 + monocytes from cryopreserved PBMCs and showed that LPS-stimulated monocytes from MS patients expressed more TNFα post B cell depletion (Fig 5d). Increases of TNFα production by LPS-stimulated CD14 + cells was similarly observed in MS patients treated with ocrelizumab by another group 30 . However, there was no significant difference in TNFα ELISA using culture supernatant (data not shown).…”
Section: Resultsmentioning
confidence: 58%
“…On the other hand, differentiation into B cells play a role in protecting the body from pathogens such as bacteria and viruses by producing antibodies and presenting antigens, but some B cells suppress autoimmune diseases by producing the inhibitory cytokine IL-10. These IL-10-producing B cells, called regulatory B cells, suppress inflammatory responses in experimental mouse models of autoimmune diseases such as inflammatory bowel disease, rheumatoid arthritis, and multiple sclerosis [31][32][33]. Since CD-1d-expressing CD5-positive B cells in spleen suppress various autoimmune diseases when administered to mice, and produce IL-10 when stimulated in vitro, these CD-1d-high CD5+ B cells are thought to be the major regulatory B cells.…”
Section: A Group Of B Cells Called Plasmablasts Control Encephalomyel...mentioning
confidence: 99%
“…As an immunosuppressive molecule, IL-10 can restrict immune responses against pathogens and microbial communities, which is a key mechanism underlying its anti-inflammatory properties. Evidence suggests that IL-10 is expressed not only in bone marrow and lymphoid lineage cells but also in tumor-associated macrophages [5], epithelial cells [6], and innate immune cells of the central nervous system [7]. This broad anti-inflammatory profile has significant effects in preventing autoimmune diseases [8], balancing neuroimmune responses [7], and cancer therapy [9].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that IL-10 is expressed not only in bone marrow and lymphoid lineage cells but also in tumor-associated macrophages [5], epithelial cells [6], and innate immune cells of the central nervous system [7]. This broad anti-inflammatory profile has significant effects in preventing autoimmune diseases [8], balancing neuroimmune responses [7], and cancer therapy [9].…”
Section: Introductionmentioning
confidence: 99%